Celebrity CEOs, digital transformation and firm performance in China: the moderating role of controlling shareholders and institutional investors - Wang, Rui; Shao, Dong; Han, Xinliang; Li, Yinyue (Frontiers in Psychology, 2023)
Background: business leaders' social status significantly impacts companies' strategic direction and performance. Digital transformation, an important tool for companies to enhance competitiveness and resilience, plays an important role in the relationship between executive background and firm performance. Objective: To investigate the impact of celebrity chief executive officers (CEO) on firm performance through digital transformation. Method: Using data from companies listed on the main boards of the Shanghai and Shenzhen Stock Exchanges between 2017 and 2021, this study explored the relationship between celebrity CEOs, digital transformation, and firm performance. Result: Celebrity CEOs significantly enhanced a firm's digital transformation. However, this effect weakened when controlling shareholders and institutional investors held more shares. Additionally, the study showed that celebrity CEOs can improve firm performance through digital transformation. These findings were robust across a range of sensitivity analyses. Conclusion: This study contributes to understanding celebrity CEOs' decision-making motivations and economic impacts from a psychological perspective while also providing valuable insights for driving digital transformation within companies.